First Report of Puccinia menthae Causing Leaf Rust on Spearmint ( Mentha spicata ) in Mexico - Solano-Báez, Alma Rosa; Flores-Moctezuma, Hilda Elizabet; Victoria, Alfonso Arellano; Félix-Gastélum, Rubén; Leyva-Mir, Santos Gerardo; Márquez-Licona, Guillermo (Plant disease, 2022)
Spearmint (Lamiaceae) is an aromatic herb widely cultivated in Mexico for its culinary, medicinal, and industrial properties. In May 2020, symptoms and signs of rust were observed in a two-ha commercial crop of spearmint in Cuautla, Morelos (18°50'26.6"N 98°57'31.9"W), Mexico. The disease incidence was 85% and the severity was 23%. Initial symptoms included chlorotic spots on the adaxial surface of the leaves. At advanced stages of the disease, necrotic spots surrounded by chlorotic halos were developed, and later the plants were defoliated. The signs were observed as numerous orange to reddish-brown erumpent pustules primarily on the abaxial surface of the leaves. Microscopic examination of the samples revealed the presence of subepidermal uredinia, erumpent, with hyaline and cylindrical paraphyses. Urediniospores (n = 50) were hyaline to light yellow, globose to obovoid, measuring 17-27  11-25 μm, including 0.6-0.7 μm wall thickness, individually supported on pedicels, echinulate, with two germinative pores. Morphological features of the fungus correspond with previous descriptions of Puccinia mentha by Kabaktepe et al. (2017). A voucher specimen (accession no. UACH448) was deposited in the Department of Agricultural Parasitology Herbarium at the Chapingo Autonomous University. To confirm identification, the 28S gene region of rDNA was amplified from one sample by a nested PCR using the primer sets Rust2inv (Aime, 2006) and LR6 (Vilgalys and Hester, 1990), and Rust28SF primers (Aime et al., 2018), and LR5 (Vilgalys and Hester, 1990) for the first and second reactions, respectively. The sequence of our specimen (GenBank accession No. OL878354) showed 100% homology (923/1304bp) with the type-specimen sequence of P. menthae (GenBank accession No. DQ354513) from Cunila origanoides from USA (Aime, 2006). Also, a phylogenetic analysis (Bayesian inference) including a published 28S dataset for Puccinia species was performed and the isolate UACH448 was grouped into a clade with P. menthae. Pathogenicity was demonstrated by spraying five ml of a suspension of urediniospores (1104 spores/ml) recovered from infected leaves onto leaves of ten healthy spearmint plants and ten noninoculated plants served as controls. All plants were maintained at temperatures from 28 to 35°C and relative humidity ranging from 70 to 80%. All inoculated plants developed the characteristic symptoms of the disease after 14 days, whereas the control plants remained symptomless. The pathogenicity test was performed twice with similar disease response. The morphological characteristics of the pathogen recovered from all the inoculated plants were identical to that originally inoculated, thus fulfilling Koch's postulates. To our knowledge, this is the first report of Puccinia menthae causing leaf rust on Mentha spicata in Mexico. This species has been previously identified in Australia (Edwards et al. 1999), New Zealand (Beresford et al. 1982), and USA (Farr and Rossman, 2021) on Mentha spicata. This disease reduces considerably the quality of peppermint plants, so it is necessary to develop management strategies.